Newcomers as Potential Drivers of Union Revitalization: Survey Evidence from Belgium - Vandaele, Kurt (Relations industrielles / Industrial Relations)

(untitled) (Département des relations industrielles de l’Université Laval, 2020)
Most people tend to join mainstream trade unions for instrumental motives and not so much for ideological reasons. This instrumentalism, together with the passivity of most union members, endangers members’ union loyalty and their willingness to act collectively. One possible way to de-emphasize the traditional model of service-oriented unionism and strengthen union commitment is to involve members in small union tasks. By partially assigning day-to-day union work to lay members, it is believed that over-stretched union representatives will be able to assign more time to implementing union policies of strategic importance.The article examines to what extent new union members are willing to voluntarily engage in union tasks inspired by organizing unionism. To test this empirically, an e-survey was conducted among first-time members of a Belgian union. Predominantly young, the respondents had been members of the union for maximum of seven years. Belgium is an interesting case for exploring how member-union ties can be boosted, as it is a quintessential example of a country with a high union density characterized by instrumental and passive membership.Following the deletion of cases with missing data, 518 observations are available for analysis. The dependent variable measures the organizing-oriented activism intent based on union tasks reflecting one-on-one organizing tactics for reaching out to potential members. A critical mass of 41.3% new members is (greatly) interested in at least one task. The regression results show that two variables derived from the planned behaviour theory significantly influence organizing-based union tasks: the pro-union context and behavioural self-control, with the latter in particular a very strong antecedent. Apart from the finding that a larger membership base is interested in performing organizing-oriented tasks, the results also, support a developmental view on union activism, i.e. a step-by-step approach to stimulating union activism via introducing various levels of union participation.